Challenges of building community-university partnerships in new poverty landscapes. Issue 1 (1st January 2017) - Howarth, Joe; Currie, Melissa Anne; Morrell, Elizabeth; Sorensen, Janni; Bengle, Tara
Abstract: This article reflects on six years of community–university partnerships (CUPs) between the Charlotte Action Research Project (CHARP), grassroots organizations, and residents of economically challenged neighborhoods in Charlotte, NC. We share lessons learned in participatory planning and community development by comparing experiences in older, urban neighborhoods with those in suburban, "new poverty landscapes." We highlight neighborhood typology, residents' choices to leave, place attachment, and sociospatial and geographic context as defining factors within CUPs. A grounded framework for evaluating CUPs is introduced, and a synthesis of interviews and CHARP archives provide insight into what to do best, and in what conditions, in partnership efforts. We conclude that community-based research should always start by listening and that sometimes moving to action research makes sense, while at other times an advocacy research route is more appropriate. We assert that the most challenged neighborhoods, despite a lack of capacity and readiness, must not be avoided.